2017
DOI: 10.5004/dwt.2017.21753
|View full text |Cite
|
Sign up to set email alerts
|

Microwave–alkaline treatment for enhanced disintegration and biodegradability of meat processing sludge

Abstract: a b s t r a c tAn increasing number of studies has been focused on the investigation of sludge treatment by microwave irradiation alone or combined with chemical methods. Besides the promising results for municipal sludge processing, the applicability of microwave pre-treatment methods is less evaluated and verified for food industry sludge, especially in continuous-flow operations. Therefore, our work is aimed at the investigation of microwave-alkaline treatment for meat processing sludge using disintegration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Beszédes et al also investigated the effects of different pH (ranging from pH 2-12) on the change in SCOD/TCOD ratio and found that at any given total irradiated microwave energy level (70 kJ/L, 150 kJ/L, 230 kJ/L) a pH of 12.0 resulted in the highest SCOD/TCOD ratio (0.33) [48]. Lemmer et al came to a similar conclusion; when combining microwave treatment with alkaline, increasing the alkaline dosage and microwave energy intensity, DD could be enhanced up to a certain point (about 50%) [49].…”
Section: Microwave-alkaline Combined Treatmentmentioning
confidence: 87%
“…Beszédes et al also investigated the effects of different pH (ranging from pH 2-12) on the change in SCOD/TCOD ratio and found that at any given total irradiated microwave energy level (70 kJ/L, 150 kJ/L, 230 kJ/L) a pH of 12.0 resulted in the highest SCOD/TCOD ratio (0.33) [48]. Lemmer et al came to a similar conclusion; when combining microwave treatment with alkaline, increasing the alkaline dosage and microwave energy intensity, DD could be enhanced up to a certain point (about 50%) [49].…”
Section: Microwave-alkaline Combined Treatmentmentioning
confidence: 87%
“…Korábbi kutatásaink során igazoltuk, hogy szennyvíziszapok mikrohullámmal történő kezelése során a lebontási hatékonyság a dielektromos paraméterek mérésével nyomon követhetővé válik (Lemmer et al, 2017). A különböző anyagok dielektromos viselkedésére hatással van a frekvencia, a hőmérséklet és az alapanyagmátrix fizikokémiai tulajdonságai (Jha et al, 2011).…”
Section: áBra: a Koi éRtékek Változása Az Alkalmazott Fe 2+ /H2o2 Aráunclassified